2020
DOI: 10.1515/jpem-2019-0438
|View full text |Cite
|
Sign up to set email alerts
|

Growth and metabolic effects of long-term recombinant human growth hormone (rhGH) treatment in short children born small for gestational age: GH-RAST study

Abstract: AbstractObjectivesTo study the efficacy and influence on metabolism of recombinant human growth hormone (rhGH) treatment in short children born small for gestational age (SGA).MethodsRetrospective, observational, multicenter study in 305 short children born SGA, treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
1
9
0
3
Order By: Relevance
“…Accordingly, Rhie et al 28 showed similar results, with the highest increase being observed during the first year of rhGH treatment, and then it gradually decreased, although it remained above 5 cm. Moreover, height was found to be normal with rhGH treatment in short SGA children with a safe metabolic profile as described Labarta et al 29 Regarding the children's growth, the mean BA-CA ratio increased significantly during rhGH treatment from baseline to Visit 4 and then stabilized until the end of the study. BA increases over time, as suggested by the increase in the BA-CA ratio (close to 1 after 6 years of treatment).…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Accordingly, Rhie et al 28 showed similar results, with the highest increase being observed during the first year of rhGH treatment, and then it gradually decreased, although it remained above 5 cm. Moreover, height was found to be normal with rhGH treatment in short SGA children with a safe metabolic profile as described Labarta et al 29 Regarding the children's growth, the mean BA-CA ratio increased significantly during rhGH treatment from baseline to Visit 4 and then stabilized until the end of the study. BA increases over time, as suggested by the increase in the BA-CA ratio (close to 1 after 6 years of treatment).…”
Section: Discussionsupporting
confidence: 55%
“…Accordingly, Rhie et al 28 showed similar results, with the highest increase being observed during the first year of rhGH treatment, and then it gradually decreased, although it remained above 5 cm. Moreover, height was found to be normal with rhGH treatment in short SGA children with a safe metabolic profile as described Labarta et al 29 …”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Labarta et al showed that in children with SGA (small for gestational age) treated with rhGH, tyreo globulina levels increased significantly but remained within the normal range. On the other hand, total and LDL cholesterol decreased in the study period [28].…”
Section: Biochemical Datamentioning
confidence: 87%